Maternal Schistosomiasis: Immunomodulatory Effects With Lasting Impact on Allergy and Vaccine Responses - Lacorcia, Matthew; Prazeres da Costa, Clarissa U. (Frontiers in Immunology, 2018)
Early exposure to immune stimuli, including maternal infection during the perinatal period, is increasingly recognized to affect immune predisposition during later life. This includes exposure to not only viral and bacterial infection but also parasitic helminths which remain widespread. Noted effects of helminth infection, including altered incidence of atopic inflammation and vaccine responsiveness, support further research into the impact these infections have for skewing immune responses. At the same time, despite a sea of recommendations, clear phenotypic and mechanistic understandings of how environmental perturbations in pregnancy and nursing modify immune predisposition and allergy in offspring remain unrefined. Schistosomes, as strong inducers of type 2 immunity embedded in a rich network of regulatory processes, possess strong abilities to shift inflammatory and allergic diseases in infected hosts, for example by generating feedback loops that impair T cell responses to heterologous antigens. Based on the current literature on schistosomiasis, we explore in this review how maternal schistosome infection could drive changes in immune system development of offspring and how this may lead to identifying factors involved in altering responses to vaccination as well as manifestations of immune disorders including allergy.